Characterization and tyrosinase activities of a mixture of β-sitosterol and stigmasterol from Bauhinia rufescens Lam - Muhammad, Aminu; Idris, Musa Maikudi; Ali, Umar; Umar, Abdulganiyu; Sirat, Hasnah Mohd (Acta Pharmaciae Indonesia, 2023)
Background: Phytosterols are steroid compounds present in plants that are similar to cholesterol in structure and functions. In this work, stem bark of Bauhinia rufescens was extracted with petroleum ether. Objective: This work aims to determine anti-tyrosinase activities of a mixture of β-sitosterol and stigmasterol from the stem bark B, rufescens for the treatment of dermatological disorders. Methods: This work is presenting isolation, characterization and anti-tyrosinase activities of a mixture of β-sitosterol and stigmasterol from the stem bark B. rufescens. The extract was subjected to chromatographic techniques to afford a phytosterol identified as a mixture of β-sitosterol and stigmasterol based on GC-MS, IR, 1HNMR and 13CNMR data. Results: The phytosterol isolated showed inhibition of tyrosinase activity at 57.1%±0.03 as compared to kojic acid with 85.0% ± 0.01 (sample concentrations of 0.1 mg/mL). Conclusion: The finding of this study revealed that, the mixture of β-sitosterol and stigmasterol has potential to be developed as tyrosinase inhibitors for the treatment of dermatological disorders.